Sosialisasi Pemilihan Kemasan Berdasarkan Jenis Produk UMKM Di Desa Lamatti Riattang, Kec. Bulupoddo, Kab. Sinjai - Andini Sabrinah Bahar; A. Besse Riyani Indah (CV. ITTC INDONESIA, 2025)
This community service activity was carried out in Lamatti Riattang Village, Bulupoddo District, Sinjai Regency, focusing on palm sugar UMKM that still face challenges in selecting packaging suitable for their product characteristics. The main problem identified was the use of improper packaging, which affected shelf life, visual quality, and consumer trust. The activity was held on July 26, 2025, using socialization and evaluation methods through pre-test and post-test. The materials delivered included the definition, function, types, and examples of appropriate packaging as well as food labeling requirements in accordance with BPOM regulations. The results showed an increase in participants’ understanding of packaging functions, the importance of moisture barriers, and the necessity of proper labeling. Participants also planned to adopt high-barrier and environmentally friendly packaging to enhance product competitiveness. Therefore, this activity contributes to improving packaging literacy, label compliance, and business sustainability among palm sugar UMKM.